Sinergi Media Pembelajaran Dengan Peran Keluarga Dalam Menumbuhkan Kejujuran Dan Tanggung Jawab Anak Usia Dini - Nelly Agustina; Winda Safitri; Latifah Latifah; Nurul Aqyla (Ar-Raihanah: Jurnal Pendidikan Islam Anak Usia Dini, 2026)
The cultivation of honesty and responsibility in early childhood is a strategic foundation for building a generation of integrity and preventing corruption from an early age. Learning media and the family role are two interconnected pillars that determine the success of character formation. However, low parental literacy, limited use of innovative learning media, and lack of synergy between schools and families often hinder the optimal internalization of these values. This study aims to analyze the use of learning media and the family role in instilling honesty and responsibility in early childhood. Using a literature review approach, this research examines various scientific sources related to learning media, family roles, and early childhood character education. The findings reveal that various learning media, including picture storybooks and audio-visual media, effectively convey moral values through concrete stories and visuals that resonate with children's world. The family plays a central role as the primary environment shaping children's character through parenting styles, role modeling, and habituation. Synergistic collaboration between the use of appropriate learning media at school and positive parenting at home creates a conducive environment for optimal internalization of honest and responsible character. Strengthening parental literacy and developing innovative learning media are key strategies to ensure children grow with a strong foundation of integrity from an early age